El Gobierno Abierto como herramienta de transparencia en los Gobiernos Autónomos Descentralizados Parroquiales del cantón Puyango, año 2023 - Guaycha Pinza, Rony Emanuel (2024)
The present research project tilled ""Open Government as a tool for transparency at the Autonomous Decentralized Parish Governments of the Puyango Canton, for the year 2023", has as its objective to answer questions related to public administration, rooted in the idea that citizens are key actors in government processes, with a focus on the open government model, transparency and citizen participation. Therefore, the main objective is to determine the level of compliance with the transparency component in the management of the parish governments of Puyango during the year 2023, without first complying with the specific ones. The aim is to check the transparency component and to compare the information provided by these institutions with the applicable regulations, in order to make a proposal for improvement that can serve as a reference model for the consolidation of the institution with a view to the GA. The methodology used is based on a qualitative approach, applying an inductive method and a non-experimental design, which are fundamental as this is considered social science research and focuses on a descriptive scope. This was done through the use of information gathering tools (bibliographic review, interviews, and observation sheets), which are valuable tools that show how deficient this level of government is in terms of compliance with state guidelines. Three parish governments (Ciano, El Arenal, El Limo) are found to be between 73% and 80% in terms of compliance with regulations, while the GAD of Mercadillo fluctuates around 91.5% and the GAD of Vicentino registers 0% due to the lack of a website. As a result, local governments are considering the involvement of citizens in state affairs as a relevant issue.